Improving Students' English Learning Outcomes through Video Based Learning Model - Abidin, Asriana Zainal; Arham, Muhammad (Educia Journal, 2023)
This article discusses learning outcomes through video-based learning. Video Based Learning method is a teaching method that focuses on student activities in learning. In the learning process with this method, the teacher only acts as a guide and facilitator who directs students to find concepts, arguments, procedures, algorithm. It is aim to improve student’s English outcomes through video based learning.